2003
DOI: 10.1177/154405910308201208
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Stem-cell-mediated Osteogenesis and Dentinogenesis

Abstract: The difference between stem-cell-mediated bone and dentin regeneration is not yet well-understood. Here we use an in vivo stem cell transplantation system to investigate differential regulation mechanisms of bone marrow stromal stem cells (BMSSCs) and dental pulp stem cells (DPSCs). Elevated expression of basic fibroblast growth factor (bFGF) and matrix metalloproteinase 9 (MMP-9, gelatinase B) was found to be associated with the formation of hematopoietic marrow in BMSSC transplants, but not in the connective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
290
1
21

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 379 publications
(319 citation statements)
references
References 23 publications
(30 reference statements)
7
290
1
21
Order By: Relevance
“…Because of the above observations, analyses by ALP activity and calcium accumulation became crucial to provide more direct evidence regarding the effect of Dex/b-GP and SMF exposure on the osteogenic differentiation of DPCs. In addition, mineralization is an essential process, both in osteogenesis and detinogenesis (Batouli et al 2003). We suggested that SMF exposure also assisted in the dentinogenesis based on the present findings in this study, though we did not study the differentiation of odontoblasts.…”
Section: Resultscontrasting
confidence: 48%
See 3 more Smart Citations
“…Because of the above observations, analyses by ALP activity and calcium accumulation became crucial to provide more direct evidence regarding the effect of Dex/b-GP and SMF exposure on the osteogenic differentiation of DPCs. In addition, mineralization is an essential process, both in osteogenesis and detinogenesis (Batouli et al 2003). We suggested that SMF exposure also assisted in the dentinogenesis based on the present findings in this study, though we did not study the differentiation of odontoblasts.…”
Section: Resultscontrasting
confidence: 48%
“…On the other hand, bone and dentin are similar in their matrix protein composition, including OPN, collagen type I, and bone sialoprotein, though their crystal structures are different (Batouli et al 2003;Shimazu et al 2002). One of the functions of those matrices seemed to support cell differentiation, whether in the osteogenesis or detinogenesis (Batouli et al 2003). We found that DPCs had the original expression of ALP and OPN genes.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…For example, synovial membrane MSCs show preferential cartilage formation in vitro when compared with bone marrow and periosteal-derived MSCs (78). Conversely, adult bone marrow MSCs appear to have osteogenesis as a default differentiation pathway (79)(80)(81)(82). Therefore, MSCs demonstrate variability in their chondrogenic and osteogenic potentials that could possibly be related to their original environments.…”
Section: Development Of Novel Therapies Based On Msc Tissue Specificimentioning
confidence: 99%